Foodborne Illness Outbreaks Reported to National Surveillance, United States, 2009–2018 - Alice E. White; Alexandra R. Tillman; Craig Hedberg; Beau B. Bruce; Michael Batz; Scott A. Seys; Daniel Dewey-Mattia; Michael C. Bazaco; Elaine Scallan Walter (Emerging Infectious Diseases, 2022)
Foodborne outbreaks reported to national surveillance systems represent a subset of all outbreaks in the United States; not all outbreaks are detected, investigated, and reported. We described the structural factors and outbreak characteristics of outbreaks reported during 2009–2018. We categorized states (plus DC) as high (highest quintile), middle (middle 3 quintiles), or low (lowest quintile) reporters on the basis of the number of reported outbreaks per 10 million population. Analysis revealed considerable variation across states in the number and types of foodborne outbreaks reported. High-reporting states reported 4 times more outbreaks than low reporters. Low reporters were more likely than high reporters to report larger outbreaks and less likely to implicate a setting or food vehicle; however, we did not observe a significant difference in the types of food vehicles identified. Per capita funding was strongly associated with increased reporting. Investments in public health programming have a measurable effect on outbreak reporting.